2012
DOI: 10.1016/j.seizure.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical aspects and quality of life as risk factors for depression in patients with epilepsy

Abstract: The purpose of this study was to investigate clinical aspects and quality of life (QOL) as risk factors for depression in patients with epilepsy. One hundred and forty outpatients with a diagnosis of epilepsy who were attending our epilepsy center participated. Patients anonymously filled out a questionnaire with clinical data related to epilepsy. Depression level was evaluated by the Hamilton Depression Rating Scale-17 (HAMD-17), and quality of life was evaluated by the Quality of Life in Epilepsy-31 (QOLIE-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Among the 43 reports on the incidence rate of depression in epilepsy, 15 were based on a population survey [ 14 , 19 22 , 25 27 , 35 , 38 , 39 , 45 , 47 , 50 , 52 ], and 28 were clinical studies [ 12 , 13 , 15 18 , 23 , 24 , 28 34 , 36 , 37 , 40 – 44 , 46 , 48 , 49 , 51 , 53 , 54 ]. In a population-based environment, the combined prevalence of epilepsy in depression patients was 27% (95% CI, 23–31), while the prevalence was 34% in the clinic (95% CI, 30–39) ( Fig 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 43 reports on the incidence rate of depression in epilepsy, 15 were based on a population survey [ 14 , 19 22 , 25 27 , 35 , 38 , 39 , 45 , 47 , 50 , 52 ], and 28 were clinical studies [ 12 , 13 , 15 18 , 23 , 24 , 28 34 , 36 , 37 , 40 – 44 , 46 , 48 , 49 , 51 , 53 , 54 ]. In a population-based environment, the combined prevalence of epilepsy in depression patients was 27% (95% CI, 23–31), while the prevalence was 34% in the clinic (95% CI, 30–39) ( Fig 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the past ten years, there have been a number of hospital-based studies regarding the prevalence of depression in PWE in different regions of China. A study in Shanghai, China [33], showed a prevalence of 25.7%, using the Hamilton Depression Rating Scale-17(HAMD-17). Studies from Beijing [34] and Sichuan [23] utilizing the Mini International Neuropsychiatric Interview (MINI) showed a prevalence of 30.2% and 26.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, psychiatric comorbidity might influence the choice of antiepileptic drug therapy, the effectiveness of the treatment, and, more generally, the patients' quality of life [2,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, particularly in the last decade, numerous studies have focused on the relationship between epilepsy and psychological disturbances [11,12]. It was generally found that depression and anxiety have the highest prevalence among patients with epilepsy [3,12,13].…”
Section: Introductionmentioning
confidence: 99%